2020
DOI: 10.1111/bjh.17130
|View full text |Cite
|
Sign up to set email alerts
|

Smoking impairs molecular response, and reduces overall survival in patients with chronic myeloproliferative neoplasms: A retrospective cohort study

Abstract: Summary The effects of smoking on the molecular response (MR) and overall survival (OS) in patients with chronic myeloproliferative neoplasms (MPNs) have not been investigated before. We analysed a historical cohort of 498 consecutive patients diagnosed with MPNs. Moreover, we analysed a subgroup of 270 consecutive patients with MPNs with > 1 measurement of the JAK2V617F variant allele frequency. The data were analysed using Kaplan–Meier plots and Cox regression analysis, along with linear regression models. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A recent study has shown that smoking impairs molecular response and reduces overall survival in MPN patients treated with rIFNα. 41…”
Section: The Future Interferon-mpn Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that smoking impairs molecular response and reduces overall survival in MPN patients treated with rIFNα. 41…”
Section: The Future Interferon-mpn Landscapementioning
confidence: 99%
“…A recent study has shown that smoking impairs molecular response and reduces overall survival in MPN patients treated with rIFNα. 41 What are the reasons for rIFNα resistance or intolerance in the MPNs?…”
Section: The Future Interferon-mpn Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…The controversy regarding the effect of smoking on sOA development and progression indeed exists [ 73 , 74 , 75 ], and studies on larger numbers of MPN patients are needed to clarify whether smoking has an effect on OA development in MPN patients. This may be even more important in light of the recent findings indicating that smoking may be responsible for MPN development, lower treatment responses, and impaired survival [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 14 ] found that the gene load of JAK2V617F mutation in patients with MPN was closely related to the severity and duration of the disease. Zhang et al [ 15 ] found that IFN- α specifically blocked the proliferation advantage of JAK2V617F mutant hematopoietic stem cells in mice, thereby preventing the development of MPN and even achieving eradication [ 16 ]. Clinical research has reported that some patients with MPN treated with IFN achieved complete hematologic and molecular biological remission [ 17 ].…”
Section: Discussionmentioning
confidence: 99%